2022
DOI: 10.1097/apo.0000000000000539
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Trauma During COVID-19 Pandemic: A Systematic Review and Meta-analysis

Abstract: Purpose: This study aimed to summarize the latest literature on the trends and incidence of ocular trauma during the COVID-19 pandemic. Design: Systematic review and meta-analysis. Methods: A systematic literature search was conducted to identify the relevant literature. The search period was between January 1, 2020, and September 20, 2021. The incidence of overall and various types of ocular trauma during the COVID-19 pandemic and the control period was analyzed. The data from different studies were poole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In addition, the study sample was limited during the study period and may not be representative for all eye injuries throughout the geographical region of Crete, as there were suspensions of work, again due to COVID-19 protective measures. As concluded by Liang et al (32) in their literature review, the COVID-19 period and the restrictions implemented led to a 67.7% drop in incidents of ocular trauma compared with previous years. Additionally, they mentioned alterations in the categories of eye injuries, since there was an increase in injuries occurring at home and a decrease of eye injuries in other activities such as work-related incidents (32).…”
Section: Final Visual Acuity (Logmar Scale)mentioning
confidence: 91%
See 2 more Smart Citations
“…In addition, the study sample was limited during the study period and may not be representative for all eye injuries throughout the geographical region of Crete, as there were suspensions of work, again due to COVID-19 protective measures. As concluded by Liang et al (32) in their literature review, the COVID-19 period and the restrictions implemented led to a 67.7% drop in incidents of ocular trauma compared with previous years. Additionally, they mentioned alterations in the categories of eye injuries, since there was an increase in injuries occurring at home and a decrease of eye injuries in other activities such as work-related incidents (32).…”
Section: Final Visual Acuity (Logmar Scale)mentioning
confidence: 91%
“…As concluded by Liang et al (32) in their literature review, the COVID-19 period and the restrictions implemented led to a 67.7% drop in incidents of ocular trauma compared with previous years. Additionally, they mentioned alterations in the categories of eye injuries, since there was an increase in injuries occurring at home and a decrease of eye injuries in other activities such as work-related incidents (32). Furthermore, Anyfantakis et al (33) noted that COVID-19 pandemic revealed the importance of communication and collaboration between the different levels of health care (primary, secondary and tertiary) in order to improve attention to the needs of patients and proposed the active operation of e-communication.…”
Section: Final Visual Acuity (Logmar Scale)mentioning
confidence: 91%
See 1 more Smart Citation
“…A systematic review and meta-analysis by Liang et al showed a reduction in overall eye injuries and substantial differences in the spectrum of ocular trauma with an increased proportion of domestic ocular trauma, while a decline in sports-related trauma during the COVID-19 pandemic. 66 This article further emphasized the need for strengthening proper health education and supervision to prevent ocular injuries beyond the COVID-19 pandemic. Conde Bachiller et al, in their study, found a significant reduction in conjunctivitis, with the most significant decrease in viral conjunctivitis cases during COVID-19.…”
Section: Positive Effects Of Covid-19mentioning
confidence: 99%
“… 65 The Royal College of Anaesthetists and Association of Anaesthetists advised using local or regional anaesthesia wherever possible, saving the resources and financial costs of personal protective equipment and preserving immune function. 66 …”
Section: Impact On Pediatric Ophthalmologistsmentioning
confidence: 99%